GREEN MARKETING AS A DRIVER OF RETAIL PERFORMANCE IN TRADITIONAL BUILDING STORES: EVIDENCE FROM SURABAYA - Dendy Tirtoadisuryo (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
This study aims to analyze the influence of green marketing on marketing performance and its impact on sales performance at traditional building material stores in Greater Surabaya. The research method used was a quantitative approach with a cross-sectional design using Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique on 120 building material stores selected through purposive sampling. The results showed that green marketing had a positive and significant effect on marketing performance (β = 0.280; p < 0.01), and marketing performance also significantly influenced sales performance (β = 0.337; p < 0.01). Furthermore, green marketing had an indirect effect on sales performance through the mediation of marketing performance (β = 0.094; p < 0.05). The conclusion of this study confirms that green marketing does not directly increase sales, but rather through improved marketing performance such as customer satisfaction, brand reputation, and trust, which ultimately drives sales performance.